2018
DOI: 10.1177/1089253218756756
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Harms of Intraoperative Transesophageal Echocardiography in Noncardiac Surgery: A Systematic Review

Abstract: Intraoperative use of transesophageal echocardiography (TEE) has become commonplace in high-risk noncardiac surgeries but the balance of benefits and harms remains unclear. This systematic review investigated the comparative effectiveness and harms of intraoperative TEE in noncardiac surgery. We searched Ovid MEDLINE, PubMed, EMBASE, and the Cochrane Library from 1946 to March 2017. Two reviewers independently screened the literature for eligibility. Studies were assessed for the risk of selection bias, confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…8,[24][25][26] Although on the higher end of this range, it may still be acceptable when the TEE provides valuable information, particularly when considering the combined major bleeding complication rate was lower at .16%. 9,21 It is notable that most of the significant bleeds had identifiable high-risk features including a history of sclerotherapy, ruptured esophageal varices within the year prior to transplant, and variceal banding the day prior to surgery. Based on their analysis, Bui et al 19 concluded that active GI bleeding and recent esophageal banding should be contraindications to TEE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,[24][25][26] Although on the higher end of this range, it may still be acceptable when the TEE provides valuable information, particularly when considering the combined major bleeding complication rate was lower at .16%. 9,21 It is notable that most of the significant bleeds had identifiable high-risk features including a history of sclerotherapy, ruptured esophageal varices within the year prior to transplant, and variceal banding the day prior to surgery. Based on their analysis, Bui et al 19 concluded that active GI bleeding and recent esophageal banding should be contraindications to TEE.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A recent systematic review found an incidence of complications from TEE of 0% to 1.7% in 5 studies of 540 patients undergoing noncardiac surgery. 9 Historically, TEE for liver transplant has been avoided due to the perceived risk of bleeding from esophageal varices. However, several recent studies, as well as increasing clinical experience, have indicated that TEE may be performed safely in many circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Despite its value, recent studies have questioned the evidence when assessing the effectiveness versus potential harms of TEE. 32 With the recent discussion of harms associated with rescue TEE, the discussion of applicability of TTE based FOCUS examination in the OR becomes relevant. A recent systematic review on intraoperative FOCUS found a high percentage of adequate image acquisition, and supported FOCUS as a method to differentiate causes of intraoperative hypotension and guide correcting interventions.…”
Section: Focus Applications For Intraoperative Assessmentmentioning
confidence: 99%
“…Fayad and colleagues systematically review the risk and benefits of intraoperative TEE in noncardiac surgery reported from 1946 to March 2017. 3 They synthesize the existing evidence to defend the use of TEE during noncardiac surgery. Zerillo and colleagues expand on previous observations reported by Fayad et al in an original study that characterizes the current use, training, and attitudes toward TEE by liver transplant anesthesiologists in the United States.…”
mentioning
confidence: 99%